Distinct carbohydrate recognition domains of an invertebrate defense molecule recognize Gram-negative and Gram-positive bacteria - Bilej, M; De Baetselier, P; Van Dijck, E; Stijlemans, B; Colige, A; Beschin, A (The Journal of biological chemistry, 2001)
Coelomic fluid of Eisenia foetida earthworms (Oligochaeta, Annelida) contains a 42-kDa defense molecule named CCF for coelomic cytolytic factor. By binding microbial antigens, namely the O-antigen of lipopolysaccharide (LPS), beta-1,3-glucans, or N,N'-diacetylchitobiose present, respectively, on Gram-negative bacteria or yeast cell walls, CCF triggers the prophenoloxidase activating pathway. We report that CCF recognizes lysozyme-predigested Gram-positive bacteria or the peptidoglycan constituent muramyl dipeptide as well as muramic acid. To identify the pattern recognition domains of CCF, deletion mutants were tested for their ability to reconstitute the prophenoloxidase cascade in E. foetida coelomic fluid depleted of endogenous CCF in the presence of LPS, beta-1,3-glucans, N,N'-diacetylchitobiose, and muramic acid. In addition, affinity chromatography of CCF peptides was performed on immobilized beta-1,3-glucans or N,N'-diacetylchitobiose. We found that the broad specificity of CCF for pathogen-associated molecular patterns results from the presence of two distinct pattern recognition domains. One domain, which shows homology with the polysaccharide and glucanase motifs of beta-1,3-glucanases and invertebrate defense molecules located in the central part of the CCF polypeptide chain, interacts with LPS and beta-1,3-glucans. The C-terminal tryptophan-rich domain mediates interactions of CCF with N,N'-diacetylchitobiose and muramic acid. These data provide evidence for the presence of spatially distinct carbohydrate recognition domains within this invertebrate defense molecule.
Keywords: Molecular Sequence Data; sekvence aminokyselin; Gram-Negative Bacteria; Carbohydrate Metabolism; Cytotoxins; DNA primery; gramnegativní bakterie; metabolismus sacharidů; grampozitivní bakterie; Base Sequence; sekvence nukleotidů; Enzyme Activation; Oligochaeta; lektiny; zvířata; Lectins; Binding Sites; Amino Acid Sequence; aktivace enzymů; tyrosinasa; Gram-Positive Bacteria; Monophenol Monooxygenase; molekulární sekvence - údaje; DNA Primers; cytotoxiny; vazebná místa; Animals